Pengaruh Transformasi Digital dan Kepatuhan Hukum Perlindungan Data terhadap Kepercayaan Pelanggan pada Platform Ritel Digital (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Nahdlatul Ulama Lampung - Robi Santoso; Riski Eka Lestari; Reni Diah Setiowati; Fatma Afriyani (INDO PUBLISHING, 2026)
Digital transformation has fundamentally reshaped the retail industry by enhancing efficiency, personalization, and transactional convenience. Nevertheless, rapid digitalization has also intensified concerns regarding personal data protection, which directly affects customer trust. This study aims to examine the effects of digital transformation and legal compliance with data protection regulations on customer trust in digital retail platforms. A quantitative explanatory survey was employed, involving 50 students from the Faculty of Economics and Business, Universitas Nahdlatul Ulama Lampung, as active users of digital retail platforms. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with R Studio. The findings reveal that both digital transformation and data protection legal compliance have positive and significant effects on customer trust, with legal compliance exerting a stronger influence. These results indicate that in a mature digital retail ecosystem, customer trust is shaped not only by technological sophistication but also by legal legitimacy and robust data protection assurance. This study enriches digital retail literature by integrating technological and legal perspectives in explaining customer trust formation.